Lumbar loading in the elite adolescent tennis serve: link to low back pain - Campbell, A.; Straker, L.; O'Sullivan, P.; Elliott, B.; Reid, M. (Medicine & Science in Sports & Exercise, 2013)
Purpose: This study aimed to quantify and compare lumbar region kinetics in kick and flat serves performed by elite, adolescent male players with and without a history of low back pain (LBP). Lumbar region kinematics, as well as racquet velocity and the position of the ball at impact, was described to facilitate kinetic data interpretation.